Long working hours and risk of 50 health conditions and mortality outcomes: a multicohort study in four European countries - Jenni Ervasti (Elsevier, 2021)
SUMMARY: Background: Studies on the association between long working hours and health have captured only a narrow range of outcomes (mainly cardiometabolic diseases and depression) and no outcome-wide studies on this topic are available. To achieve wider scope of potential harm, we examined long working hours as a risk factor for a wide range of disease and mortality endpoints. Methods: The data of this multicohort study were from two population cohorts from Finland (primary analysis, n=59 599) and nine cohorts (replication analysis, n=44 262) from Sweden, Denmark, and the UK, all part of the Individual-participant Meta-analysis in Working Populations (IPD-Work) consortium. Baseline-assessed long working hours (≥55 hours per week) were compared to standard working hours (35-40 h). Outcome measures with follow-up until age 65 years were 46 diseases that required hospital treatment or continuous pharmacotherapy, all-cause, and three cause-specific mortality endpoints, ascertained via linkage to national health and mortality registers. Findings: 2747 (4·6%) participants in the primary cohorts and 3027 (6·8%) in the replication cohorts worked long hours. After adjustment for age, sex, and socioeconomic status, working long hours was associated with increased risk of cardiovascular death (hazard ratio 1·68; 95% confidence interval 1·08-2·61 in primary analysis and 1·52; 0·90-2·58 in replication analysis), infections (1·37; 1·13-1·67 and 1·45; 1·13-1·87), diabetes (1·18; 1·01-1·38 and 1·41; 0·98-2·02), injuries (1·22; 1·00-1·50 and 1·18; 0·98-1·18) and musculoskeletal disorders (1·15; 1·06-1·26 and 1·13; 1·00-1·27). Working long hours was not associated with all-cause mortality. Interpretation: Follow-up of 50 health outcomes in four European countries suggests that working long hours is associated with an elevated risk of early cardiovascular death and hospital-treated infections before age 65. Associations, albeit weak, were also observed with diabetes, musculoskeletal disorders and injuries. In these data working long hours was not related to elevated overall mortality. Funding: NordForsk, the Medical Research Council, the National Institute on Aging, the Wellcome Trust, Academy of Finland, and Finnish Work Environment Fund.